Prototype development of information system based on distance using best-first search technique for UiTM Shah Alam / Agnes Anak Georges - Anak Georges, Agnes (2005)
This thesis reviews UiTM Shah Alam's students, lecturer and visitors destination on the information system, and examines the role and design of maps for interactive map. The thesis aim is to design a prototype of UiTM guidance based on distance by using best first search technique. In order to develop this prototype, developer had to collect data regarding UiTM Shah Alam such as the road plan to faculties, and administration building. The methodology for deriving a sample of current official user is presented, and the result of a content analysis, performed on the sample of interactive maps, is discussed. In order to gain insight into user preferences for UiTM's map use and design, and to access the effectiveness of the sample interactive map, user survey was conducted by answer the questionnaires. The results of the survey are reviewed. The thesis concludes by presenting suggestions for future people destination design, and the design, use, and implementation of interactive map.